Análise de desempenho de voo em subida e cruzeiro da aeronave não tripulada elétrica EOLO - Silva, Thamires Rabelo da [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Este trabalho apresenta a análise de desempenho do Veículo Aéreo Não Tripulado (VANT) elétrico EOLO, uma plataforma experimental de asa flexível desenvolvida para pesquisa em aeroelasticidade e dinâmica de voo. O objetivo principal é caracterizar o envelope operacional da aeronave e validar sua eficiência energética nas fases de subida e cruzeiro. A metodologia integra a modelagem analítica e simulações numéricas, unindo modelos aerodinâmicos não lineares às equações de desempenho de propulsão elétrica. Na fase de subida, determinou-se a razão de subida ótima considerando as limitações térmicas e de corrente do sistema motor-hélice. Para o cruzeiro, serão identificadas as velocidades de máxima eficiência, resultando em uma autonomia máxima estimada de 64 minutos e um alcance máximo de aproximadamente 56 km, para um voo de 1000 metros de altitude. Os resultados validam a viabilidade do EOLO para missões de longa duração e fornecem os parâmetros críticos para a operação segura dentro dos limites estruturais e energéticos do projeto.

This work presents a comprehensive performance analysis of the electric Unmanned Aerial Vehicle (UAV) EOLO, a flexible-wing experimental platform developed for research in aeroelasticity and flight dynamics. The main objective was to characterize the aircraft’s operational envelope and validate its energy efficiency during climb, cruise, and glide phases. The methodology integrated analytical modeling and numerical simulations, coupling non-linear aerodynamic models with electric propulsion performance equations. In the climb phase, the optimal rate of climb was determined considering the thermal and current limitations of the motor-propeller system. For the cruise phase, maximum efficiency speeds were identified, resulting in an estimated maximum endurance of 64 minutes and a maximum range of approximately 56 km. The glide phase analysis, performed by integrating longitudinal equations of motion, confirmed the aircraft’s dynamic stability. Simulations demonstrated an average sink rate of 0.57 m/s and stable behavior in the phugoid mode, and satisfactory damping of perturbations. The results validate the viability of EOLO for long-endurance missions and provide critical parameters for safe operation within the project’s structural and energetic limits.
Analysis of flight performance during climb and cruise of the EOLO electric unmanned aircraft
Keywords: Drone; Desempenho; Engenharia de voo; Vôo; Eletricidade na aeronáutica